Predictive Factors for HBsAg Seroconversion Following Acute Hepatitis B Virus Infection: A Multicenter BUHASDER Study - Caydasi, Ozge; Engin, Derya Ozturk; Karasahin, Omer; Batirel, Ayse; Dolu, Suleyman; Deniz, Muge Toygar; Kose, Sukran (Mdpi, 2025)
Experience with the effect of antiviral therapy on HBsAg seroconversion in acute hepatitis B is limited. We aimed to evaluate the factors affecting HBsAg seroconversion in patients with acute hepatitis B (AHB) receiving antiviral treatment. We performed a retrospective and multicenter study involving 107 adult patients who received antiviral treatment for AHB between January 2018 and December 2023. The median age was 48 (min-max, 18-91) years, and 66.3% of the patients were male; 70 patients with 24-week follow-up (15 patients without HBsAg seroconversion versus 55 patients with HBsAg seroconversion) were compared based on HBsAg seroconversion status. Multivariate logistic regression analysis revealed that age was independently associated with HBsAg seroconversion (odds ratio = 0.926; 95% confidence interval (CI) 0.874 to 0.981; p = 0.009). A one-year increase in age was associated with a 0.926-fold decrease in HBsAg seroconversion. In conclusion, age was an independent predictor of HBsAg seroconversion following acute hepatitis B virus infection.
Keywords: acute hepatitis B; entecavir; HBsAg seroconversion; predictor; tenofovir